2000
DOI: 10.1095/biolreprod63.5.1271
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Protein Kinase Cα in the Lysophosphatidic Acid-Induced Bovine Sperm Acrosome Reaction and Phospholipase D1 Regulation1

Abstract: Protein kinase C (PKC) has been implicated in the sperm acrosome reaction. In the present study, we demonstrate induction of the acrosome reaction and activation of sperm PKCalpha by lysophosphatidic acid (LPA), which is known to induce signal transduction cascades in many cell types via binding to specific cell-surface receptors. Under conditions by which LPA activates PKCalpha, there is significant stimulation of the acrosome reaction, which is inhibited by PKC inhibitors. Protein kinase Calpha belongs to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 51 publications
5
28
0
Order By: Relevance
“…Activation of PKC by ATPe was also found in CHO cells [56]. In recent papers, we showed that one of the cPKC isoforms, PKC␣, is involved in the bovine sperm AR [42,43]. Here, we provide further support for this notion by showing that ATPe activates PKC␣, and that the AR induced by ATPe is inhibited by a PKC-specific inhibitor.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Activation of PKC by ATPe was also found in CHO cells [56]. In recent papers, we showed that one of the cPKC isoforms, PKC␣, is involved in the bovine sperm AR [42,43]. Here, we provide further support for this notion by showing that ATPe activates PKC␣, and that the AR induced by ATPe is inhibited by a PKC-specific inhibitor.…”
Section: Discussionsupporting
confidence: 73%
“…In our recent publications, we showed that the Ca 2ϩ -dependent PKC␣ isoform is involved in the mechanism of bovine sperm AR [42,43]. The involvement of the P 2y receptor suggests that the activation of PLC results in the hydrolysis of phosphatidyl inositol to produce diacylglycerol (DAG) and inositol 1,4,5-tris-phosphate (IP 3 ).…”
Section: Involvement Of Pkc␣ In Atp-induced Armentioning
confidence: 99%
“…One study demonstrated that LPP-1 overexpression resulted in impaired spermatogenesis (264), suggesting that the presence of LPA may be important in sperm development. There is also evidence for LPA involvement in sperm motility (265), although triple genetic deletion of LPA [1][2][3] showed no detectable defi cits in sperm motility. However, deletion of LPA 1-3 did result in decreased germ cell survival and increased prevalence of azoospermia in aging mice (264).…”
Section: Reproductive System and Infertilitymentioning
confidence: 99%
“…PLD1 (not PLD2) is localized in the outer acrosome membrane “suggesting its possible involvement in the AR” (Garbi et al, 2000). The authors also suggest that acrosomal PLD1 is involved in PKCα activation and that PA is “a fusogenic compound that may stimulate the fusion between the outer acrosomal and the plasma membrane leading to acrosomal exocytosis.”…”
Section: Pld and Pa Are Associated With Membrane Fusionmentioning
confidence: 99%